The epidemiology of postnatal depression in Ethiopia: a systematic review and meta-analysis - Bereket Duko; Dereje Wolde; Yonas Alemayehu (BMC, 2020)
Abstract Background Postnatal depression is among the common mental health problems that occur during the postnatal period. However, it is left undiagnosed in low- and middle-income countries including Ethiopia. Therefore, this systematic review and meta-analysis aimed to systematically summarize the available evidence on the epidemiology of postnatal depression in Ethiopia and suggest recommendations for future clinical practice. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed to conduct this systematic review and meta-analysis. We searched PubMed, SCOPUS, EMBASE and Google Scholar databases for the relevant articles that assessed the prevalence of postnatal depression in Ethiopia. We used a random-effect model to conduct a meta-analysis. We conducted a subgroup and sensitivity analysis to explore the source of heterogeneity. Cochrane Q- and the I2-test were used to check the heterogeneity of the included studies. The presence of publication bias was also checked by visual inspection of symmetry and Egger's test. Results The pooled estimated prevalence of postnatal depression in Ethiopia was 20.1% (95% CI 12.7-30.2). The pooled prevalence of postnatal depression in the studies that were conducted in community settings and used the Patient Health Questionnaire to assess postnatal depression [16.6% (95% CI 8.90-28.99)] was lower than the prevalence in studies based in institutions and that used the Edinburgh Postnatal Depression Scale [23.2% (95% CI 14.50-28.5)]. Further, in a leave-one-out sensitivity analysis the prevalence of postnatal depression ranges between 15.4% and 25.4%. Unplanned pregnancy [AOR = 3.46, 95% CI (2.37-5.04)], age between 15-24 years [AOR = 1.72, 95% CI (1.11-2.68)], marital problems [AOR = 3.07, 95% CI (2.36-3.99)], experiencing the death of infant [AOR = 3.41, 95% CI (1.91-6.09)] and history of substance use [AOR = 3.47, 95% CI (2.17-5.56)] were associated with the increased odds of postnatal depression in Ethiopia. Conclusion The prevalence of postnatal depression in Ethiopia was high. Therefore, the concerned body should give due attention to improve reproductive health services through early detection of risk factors of postnatal depression.